2018
DOI: 10.1152/physiol.00014.2018
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Bodies and the Integrated Cardiorespiratory Response to Hypoxia

Abstract: Advances in our understanding of brain mechanisms for the hypoxic ventilatory response, coordinated changes in blood pressure, and the long-term consequences of chronic intermittent hypoxia as in sleep apnea, such as hypertension and heart failure, are giving impetus to the search for therapies to "erase" dysfunctional memories distributed in the carotid bodies and central nervous system. We review current network models, open questions, sex differences, and implications for translational research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 265 publications
(291 reference statements)
0
25
0
Order By: Relevance
“…Briefly, three main sensory stimuli that alert the brain during apnea are hypoxia, hypercapnia and negative air pressure in the airways created due to increased respiratory efforts (sensed by mechanoreceptor fibers in vagus) during apneas (White, 2006, 2017). The carotid body primarily senses the hypoxia and to a lesser extent the hypercapnia, and transmits that information to the nucleus of the solitary tract (NTS) via the carotid sinus branch of the glossopharyngeal nerve (Massari et al, 1996; Lindsey et al, 2018). In addition, the chemosensory neurons in the retrotrapezoid nucleus (RTN) directly sense the CO2, and these project in parallel to the NTS to the ventrolateral medulla (VLM- pattern generator for breathing), and parabrachial nucleus (PB- relay node for visceral sensory information from the brainstem to the forebrain) (Dean et al, 1989; Herbert et al, 1990; Finley and Katz, 1992; Massari et al, 1996; Guyenet et al, 2010a; Bochorishvili et al, 2012; Guyenet and Bayliss, 2015; Lindsey et al, 2018; Figure 1A).…”
Section: Introductionmentioning
confidence: 99%
“…Briefly, three main sensory stimuli that alert the brain during apnea are hypoxia, hypercapnia and negative air pressure in the airways created due to increased respiratory efforts (sensed by mechanoreceptor fibers in vagus) during apneas (White, 2006, 2017). The carotid body primarily senses the hypoxia and to a lesser extent the hypercapnia, and transmits that information to the nucleus of the solitary tract (NTS) via the carotid sinus branch of the glossopharyngeal nerve (Massari et al, 1996; Lindsey et al, 2018). In addition, the chemosensory neurons in the retrotrapezoid nucleus (RTN) directly sense the CO2, and these project in parallel to the NTS to the ventrolateral medulla (VLM- pattern generator for breathing), and parabrachial nucleus (PB- relay node for visceral sensory information from the brainstem to the forebrain) (Dean et al, 1989; Herbert et al, 1990; Finley and Katz, 1992; Massari et al, 1996; Guyenet et al, 2010a; Bochorishvili et al, 2012; Guyenet and Bayliss, 2015; Lindsey et al, 2018; Figure 1A).…”
Section: Introductionmentioning
confidence: 99%
“…respiratory-sympathetic coupling under these conditions is a result of synchronized activation of respiratory and sympathetic medullar neurons (Zoccal, 2015;Lindsey et al, 2018). In the present study, the growth of CRC at rest in normobaric hypoxia in humans is shown for the first time, and the prevailing frequencies at which it occurs were highlighted.…”
Section: Discussionmentioning
confidence: 54%
“…It has been shown previously that acute hypoxia causes an increase in sympathetic activity and an increase in sympatho-respiratory coupling in rodents ( Dick et al, 2014 ). The enhanced respiratory-sympathetic coupling under these conditions is a result of synchronized activation of respiratory and sympathetic medullar neurons ( Zoccal, 2015 ; Lindsey et al, 2018 ). In the present study, the growth of CRC at rest in normobaric hypoxia in humans is shown for the first time, and the prevailing frequencies at which it occurs were highlighted.…”
Section: Discussionmentioning
confidence: 99%
“…The hypercapnia, hypoxia, and negative intrapharyngeal-airway pressure created by inspiratory effort against a blocked airway induce progressive activation of the GG. The Sol, PB, and ventrolateral medulla receive projections from chemosensory neurons in the retrotrapezoid nucleus, so they sense the hypercapnia, hypoxia, and other chemosensory information caused by apnea [44]. Our results indicated that all of these regions affect GG activity by innervating HMNs directly.…”
Section: Neural Circuitry Underlying Modulation Of Hmn Activity Durinmentioning
confidence: 67%